Comprehensive Pan-Cancer Analysis Reveals the Potential Biological, Immunological, and Prognostic Value of NKG2A - Rong, Yao; Wang, Yongfeng; Tang, Mingzheng; Zhang, Guiqian; Yuan, Yuan; Dong, Fengyuan; Wu, Zhihang; Ma, Guorong; Liu, Songhua; Zhao, Xiashuang; Cai, Hui (Analytical cellular pathology (Amsterdam), 2023)
Background. NKG2A (KLRC1) belongs to the NKG2 family, which has been shown to affect the activity of natural killer (NK) cells and CD8T cells. However, a comprehensive biological analysis and exploration of NKG2A in different cancers is lacking and this needs to be further investigated. Methods. A comprehensive pan-cancer analysis of NKG2A was performed based on multiple databases. The Cancer Genome Atlas (TCGA) and Genotype–Tissue Expression (GTEx) databases were used to analyze the expression profile of NKG2A in pan-cancer. The relevance of NKG2A to the prognosis of different cancers was assessed using Kaplan–Meier survival analysis. In addition, we explored the correlation between NKG2A expression and gene mutations, pathological staging, tumor-infiltrating immune cells (TIICs), DNA methyltransferase (DNMT) genes, tumor mutation burden (TMB), microsatellite instability (MSI), mismatch repair (MMR), and immune checkpoints (ICPs). Finally, the expression levels of NKG2A in several cancer cell lines were verified by qRT-PCR. Results. Pan-cancer comprehensive analysis showed that NKG2A expression levels were significantly different between multiple cancers and corresponding normal tissues. The differential expression of NKG2A was related to the prognosis and pathological staging of patients with multiple cancers, and was closely related to the excessive infiltration of immune cells and the regulation of ICP genes in the tumor microenvironment (TME). In addition, TMB, MSI, MMR, and DNMT genes in many cancer types are also affected by NKG2A expression. Gene set enrichment analysis (GSEA) showed that NKG2A was associated with multiple immune-related functions and pathways in malignant tumors. qRT-PCR results showed that NKG2A was underexpressed in liver, gastric, and colon cancer cell lines compared to normal cells, which was consistent with bioinformatics analysis. Conclusion. The present study suggests that NKG2A may be a potential predictive biomarker for cancer immune response and prognosis.